PERLINDUNGAN NOTARIS MELALUI AKTA YANG DIBUATNYA TERHADAP KEMUNGKINAN SENGKETA DIKEMUDIAN HARI - Marvin, Marvin; Latumeten, Pieter (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The Notary Deed should be able to protect the Notary who made the authentic deed. This is due to the skills of irresponsible parties who take advantage of the authority of a notary in making authentic deeds that function as perfect evidence. The emphasis in this paper is related to the reality that occurs in the community, especially with the presence of fake appearing figures and the use of fake documents as the basis for making a notarial deed carried out by the appearer. This results in the Notary being the party being sued and/or co-defendant and/or suspected of committing a violation and/or criminal act of forgery related to the deed Notary made. Therefore, the Notary in making the deed needs to meet certain criteria which aim to protect the Notary as the maker of the deed against errors and/or violations committed by the parties.